Organizational training within digital transformation: The ToOW model - Ferreira, Maria João (2018)
Information systems and technologies (IST) are the essence of up-to date organizations, and changes in this field are occurring at an uncontrollable pace, interrupting traditional business models and forcing organisations to implement new models of business. Social media tools represent a subset of these technologies that contribute to digital transformation (DT) of organizations and which are already used within organizational training contexts. However, the adoption of social media tools, by itself, does not guarantee such a transformation; changes in the organization’s culture and behaviour are also needed. Taking advantage of the DT technology enablers and realising the need for updated approaches to address organizational workers’ training, we propose a model to guide organizational training within DT. The model, called Training of Organizational Workers (ToOW), addresses the 2nd layer of the mobile Create, Share, Document and Training (m_CSDT) framework formerly described. The advantages foreseen for the model usage are twofold. On the one hand, the model acknowledges the crucial role that an organization plays in promoting a culture of continuous learning/training of its employees; on the other hand, the model provides guidance on setting up the training strategies and activities, as well as on the monitoring of training results achieved, whichare measured according to the performance metrics considered within the organizational strategy.